DETEMINANTS OF STUDENT SATISFACTION AT DEHASEN UNIVERSITY OF BENGKULU - Guspita, Dwi Eka (Business Education Program of Universitas Pendidikan Indonesia, 2021)
Educate service is reflection and implementation of a program or the management in an educational institution. Low and high student satisfaction depends on the quality of education service in an institution. Student satisfaction is the crucial thing for education institution sustainable due to student satisfaction have resulted of alumni that affected institution accreditation, especially private university. It can reduce the grade of institution accreditation if student satisfaction decrease. Hence, the effect is so high to sustain educating service. This research aimed to measure and find associated with student satisfaction. This research was used survey research taken at the Dehasen University of Bengkulu. The respondents were 200 people that calculated by simple random sampling. The analysis was used univariate, and regression. The prevalence unsatisfied of students was 26%. It means that unsatisfied of students still high. The factors had associated with student satisfaction were tangibles (p: 0.001) and reliability (p: 0.002). Dehasen University should evaluate dan change the education system and should grow studentsâ€™ beliefs. That can increase student satisfaction with tangibles and reliability.Â Â